2020
DOI: 10.3390/ijms21072363
|View full text |Cite
|
Sign up to set email alerts
|

The Subcellular Localization and Oligomerization Preferences of NME1/NME2 upon Radiation-Induced DNA Damage

Abstract: Nucleoside diphosphate kinases (NDPK/NME/Nm23) are enzymes composed of subunits NME1/NDPK A and NME2/NDPK B, responsible for the maintenance of the cellular (d)NTP pool and involved in other cellular processes, such as metastasis suppression and DNA damage repair. Although eukaryotic NDPKs are active only as hexamers, it is unclear whether other NME functions require the hexameric form, and how the isoenzyme composition varies in different cellular compartments. To examine the effect of DNA damage on intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 83 publications
(106 reference statements)
1
13
0
Order By: Relevance
“…The study of NME1-NME2 interaction in vivo by the use of FRET/FLIM revealed that NME1 and NME2 co-localize, with irradiation-induced DNA damage causing a small shift in NME1/NME2 homo-and hetero-isoenzyme ratios [83]. In agreement with this, it has been observed more recently that NME3 stimulates mitochondrial elongation dependent on oligomerization activity [84].…”
Section: Assembly and Oligomerization Of Human Nmessupporting
confidence: 61%
“…The study of NME1-NME2 interaction in vivo by the use of FRET/FLIM revealed that NME1 and NME2 co-localize, with irradiation-induced DNA damage causing a small shift in NME1/NME2 homo-and hetero-isoenzyme ratios [83]. In agreement with this, it has been observed more recently that NME3 stimulates mitochondrial elongation dependent on oligomerization activity [84].…”
Section: Assembly and Oligomerization Of Human Nmessupporting
confidence: 61%
“…Numerous studies have confirmed a possible role in DNA repair for NN23-H1 and NM23-H2, human orthologous of TcNDPK1, through the base excision repair and nucleotide excision repair pathways (BER and NER, respectively) and also in DSB repair. (6,28) Consistent with this role, NM23-H1 was reported to be peri-nuclear and nuclear and rapidly translocate to sites of DNA damage Fig. 4: TcPARP activity.…”
Section: Discussionmentioning
confidence: 71%
“…Numerous studies have confirmed a possible role in DNA repair for NN23-H1 and NM23-H2, human orthologous of TcNDPK1, through the base excision repair and nucleotide excision repair pathways (BER and NER, respectively) and also in DSB repair. 6 , 28 Consistent with this role, NM23-H1 was reported to be peri-nuclear and nuclear and rapidly translocate to sites of DNA damage in the nucleus. 4 , 5 The mechanism underlying nuclear translocation is poorly understood because these enzymes lack a canonical nuclear localisation signal, although passive diffusion is also expected due to their small molecular weight.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations